Primary HIV Drug Resistance among Recently Infected Cases of HIV in North-West India - C. K. Chauhan; P. V. M. Lakshmi; V. Sagar; A. Sharma; S. K. Arora; R. Kumar (AIDS Research and Treatment)
Background. Antiretroviral treatment may lead to the emergence of HIV drug resistance, which can be transmitted. HIV primary drug resistance (PDR) is of great public health concern because it has the potential to compromise the efficacy of antiretroviral therapy (ART) at the population level. Objective. To estimate the level of primary drug resistance among recently infected cases of HIV in 6 ART centres of North-Western India from September 2014 to June 2016. Methods. The level of primary drug resistance was studied among 37 recently infected HIV cases identified by Limiting antigen (Lag) avidity assay based on modified Recent Infection Testing Algorithm (RITA). The reverse transcriptase region of HIV-1 pol gene (1-268 codons) was genotyped. The sequences were analyzed using the Calibrated Population Resistance (CPR) tool of Stanford University HIV drug resistance (DR) database to identify drug resistance. Results. Among 37 isolates studied, 6 (16.2%) samples showed primary drug resistance (PDR) against reverse transcriptase (RT) inhibitor. The proportion of primary drug resistance was 22.2% (2/9) among female sex workers, 14.3% (1/7) among men having sex with men, and 14.3% (3/21) among injecting drug users. Observed mutations were K219R, L74V, K219N, and Y181C. Injecting drug user (IDU) has showed resistance to either nucleoside/nucleotide reverse transcriptase inhibitors (NRTI) or nonnucleotide reverse transcriptase inhibitors (NNRTI). Conclusion. Resistance to either NRTI or NNRTI among the recently is a new challenge that needs to be addressed. The fact that both Y181C isolates are IDUs is important and represents 2/21 (~10%) NNRTI drug resistance. Surveillance for primary drug resistance (PDR) needs to be integrated into next generation of HIV surveillance as access to ART is increasing due to introduction of test and treat policy.